Evaluating the use of commercial drug-specific calibrators for determining PT and APTT reagent sensitivity to dabigatran and rivaroxaban - Gosselin, Robert C.; Adcock, Dorothy; Hawes, Emily M.; Francart, Suzanne J.; Grant, Russell P.; Moll, Stephan (Thrombosis and Haemostasis, 2015)
Suitable laboratory methodologies for quantifying the non-vitamin K oral anticoagulants (NOAC) include liquid chromatography-tandem mass spectrometry (LC-MS/MS) or drug-calibrated assays such as the dilute thrombin time for dabigatran or anti-Xa measurements for rivaroxaban. In situations when these tests are unavailable, it has been suggested that using commercial drug calibrators on APTT and PT assays would theoretically provide reagent sensitivity to these drugs. The purpose of this study was to determine whether commercial drug calibrators deliver similar reagent sensitivity information as samples from patients receiving dabigatran or rivaroxaban as part of their routine care. Two laboratory sites tested commercial calibrator material for dabigatran and rivaroxaban (Hyphen Biomedical) using PT and APTT reagents and data was compared to samples collected from patients taking NOACs that were quantified by LC-MS/MS. Correlation statistics and calculating the amount of drug required to double the clotting time of normal plasma were performed. All drug calibrator material correlated more strongly (R2> 0.95) for any reagent/drug combination than patient samples (R2 ranged from 0.29–0.86). Dabigatran calibrator results and patient data were equivalent for SynthASil and PTT-A APTT reagents. The dabigatran and rivaroxaban calibrator material over-estimated drug sensitivity for all PT reagents when compared to sensitivity data calculated based on drug levels obtained by LC-MS/MS from patient samples. In conclusion, drug-specific calibrators overestimated reagent sensitivity which may underestimate invivo drug concentration in a given patient. Further studies are required to assess whether this method of determining relative sensitivity of NOAC on routine coagulation assays should be recommended.
Keywords: Dabigatran; rivaroxaban; drug calibrators; reagent sensitivity